Physical Activity and Cancer - Courneya, Kerry S.; Courneya, Kerry S.; Friedenreich, Christine M.; Friedenreich, Christine M. (Recent Results in Cancer Research, 2011)
This book explores in depth the relation between physical activity and cancer control, including primary prevention, coping with treatments, recovery after treatments, long-term survivorship, secondary prevention, and survival. The first part of the book presents the most recent research on the impact of physical activity in preventing a range of cancers. In the second part, the association between physical activity and cancer survivorship is addressed. The effects of physical activity on supportive care endpoints (e.g., quality of life, fatigue, physical functioning) and disease endpoints (e.g., biomarkers, recurrence, survival) are carefully analyzed. In addition, the determinants of physical activity in cancer survivors (e.g., medical, social cognitive, environmental) are discussed, and behavior change strategies for increasing physical activity in cancer survivors (e.g., counseling, print materials) are appraised. The final part of the book is devoted to further special topics, including the relation of physical activity to pediatric cancer survivorship and to palliative cancer care.